Training of Digital Learning Resources for Islamic School Teachers: A Community Service - Elis Homsini Maolida; Vina Aini Salsabila; Anisa Sofarini; Nia Kurniawati (INCOME: Indonesian Journal of Community Service and Engagement, 2026)
The use of digital tools has become an integral part of teaching and learning at various levels of education. Rapid developments in digital technology have opened the door to creating more interacting, engaging, and effective learning tools. Teachers, as the main agents in imparting knowledge, are in need of understanding and integrating digital-based learning media in the teaching and learning process. With this in mind, this training initiative addresses the pressing need for modernizing pedagogical approaches in the educational system in the Islamic schools. The training aims to bridge the gap between traditional teaching methods and contemporary educational tools, fostering a more engaging and inclusive learning environment. The 50 teachers from Madrasah Ibtidaiyah (MI) , Tsanawiyah (MTs), and Aliyah (MA) Asy-Syifa, participated in this training. The face-to-face training, held on November 2, 2023, comprised several sessions: a session of digital literacy sharing, followed by acquainting participants with the LearningApps, exploration of Canva features for creating and designing learning materials, as well as photo and video editing Kinemaster application, providing insight into the digitalization of students’ learning products. Each session concluded with hands-on practice, allowing teachers to experience the apps firsthand. The final session prioritized reflection, prompting participants to contemplate their training takeaways and strategize how they would apply newfound knowledge and skills in practical teaching contexts. The evaluation showed that the training met its intended goals. Consistent attendance across all sessions, active involvement, positive responses, and the submission of digital teaching artifacts demonstrated strong engagement and positive learning outcomes.